NUTRIENT RELEASE FROM GREEN MANURE UNDER DIFFERENT SUN-EXPOSED FACES - Mendonça, Eduardo de Sá; Moura, Waldenia de Melo; Guimarães, Gabriel Pinto; Burak, Diego Lang (Coffee Science - ISSN 1984-3909, 2018)
The evaluation of the decomposition of plant residues added to the soil for green manures allows better understanding of the nutrient supply for coffee. The aim of this study was to determine the decomposition constant (κ), the halflifetime (t1/2) and the nutrient release from legumes and spontaneous plant under two environmental conditions of sun-exposure in the Zona da Mata of Minas Gerais state. The experimental unit located in Araponga has northwest sun-exposure face and the experimental unit located in Pedra Dourada has the south sun-exposure face. The experimental design was a randomized block in a 2 x 8 x 6 factorial (two environments facing sun-exposure, 8 green manures and 6 residue decomposition assessment times), with four replicates. The results showed that κ and t1/2 of the evaluated green manures did not differ between the northwestern face (highest altitude, temperature and incident light) and the south face (lower altitude, temperature and incident light). The κ difference obtained between all green manures was due to its chemical and biochemical composition. At the end of the evaluation period of 240 days an average of 62,3 and 63,1% N; 99,4 and 99,5% P and 92,8 and 93,3% K were released from the green manures of the northwest and south faces respectively. The most promising legume in the total nutrients release on the northwest face was D. lablab with 74,6; 10,9 and 69,0 kg ha-1 of N, P and K, respectively. To the south face the most promising legume was C. spectabilis with 69,1; 10,4 and 47,9 kg ha-1 of N, P and K, respectively.